Impact of active lifestyle on the primary school children saliva microbiota composition - Mancini, Annamaria; Cerulli, Claudia; Vitucci, Daniela; Lasorsa, Vito Alessandro; Parente, Daniela; Di Credico, Andrea; Orrù, Stefania; Brustio, Paolo Riccardo; Lupo, Corrado; Rainoldi, Alberto; Schena, Federico; Capasso, Mario; et al. (Frontiers in Nutrition, 2023)
The aim of the study was to evaluate the effects of Active or Sedentary lifestyle on saliva microbiota composition in Italian schoolchildren. Methods 114 male and female children (8-10 years) belonging to five primary schools in the neighborhoods of Turin were classified as active (A) or sedentary (S) based on PAQ-C-It questionnaire. PCR amplification of salivary DNA targeted the hypervariable V3-V4 regions of the 16S rRNA bacterial genes. DADA2 workflow was used to infer the Amplicon Sequence Variants and the taxonomic assignments; the beta-diversity was obtained by PCoA with the UniFrac method; LEfSe algorithm, threshold at 5%, and Log LDA cutoff at ± 0.5 were used to identify differently abundant species in A compared to S saliva sample. Daily food intake was assessed by 3-Days food record. The metabolic potential of microbial communities was assessed by PICRUSt. Results No significant differences were found in individual’s gender distribution (p=0.411), anthropometry, BMI (p>0.05), and all diet composition between A and S groups (p>0.05). 8 species were differently abundant: Prevotella nigrescens (LDA score = -3.76; FDR = 1.5x10-03), Collinsella aerofaciens (LDA score = -3.17; FDR = 7.45x10-03), Simonsiella muelleri (LDA score = -2.96; FDR = 2.76x10-05), Parabacteroides merdae (LDA score = -2.43; FDR = 1.3x10-02) are enriched in the A group; Gemella parahaemolysans, Prevotella aurantiaca (LDA score = -3.9; FDR = 5.27x10-04), Prevotella pallens (LDA score = 4.23; FDR = 1.93x10-02), Neisseria mucosa (LDA score = 4.43; FDR = 1.31x10-02; LDA score = 2.94; FDR = 7.45x10-03) are enriched in the S group. A prevalence of superpathway of fatty acid biosynthesis initiation (E. coli) and catechol degradation II (meta-cleavage pathway) was found in saliva from A compared to S children. Conclusion Our results showed that active children had an enrichment of species and genera mainly associated with a healthier profile. By contrast, the genera and the species enriched in the sedentary group could be linked to human diseases.